2020
DOI: 10.13075/ijomeh.1896.01565
|View full text |Cite
|
Sign up to set email alerts
|

Perceived indoor air quality and psychosocial work environment in office, school and health care environments in Finland

Abstract: The study examined the extent and prevalence of perceived indoor environment-related (IE-related) symptoms environmental complaints and psychosocial work environmental factors in Finnish office, school and health care environments. Material and Methods: The data were collected from non-industrial workplaces (N = 455) in 2011-2012 and 2015-2017 using the Finnish Institute of Occupational Health's Indoor Air Questionnaire (IA Questionnaire). Suspicion of IE-related problems was reported in 59% of workplaces. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…So far, numerous studies have been carried out to clarify the potential importance of different aspects of the environment for health and healing, such as indoor air quality and noise (16)(17)(18)(19). As one of the most intuitive environmental factor, it is well-known that light may exert a signi cant impact on patients' physical and psychological well-being in various direct or indirect ways (20).…”
Section: Discussionmentioning
confidence: 99%
“…So far, numerous studies have been carried out to clarify the potential importance of different aspects of the environment for health and healing, such as indoor air quality and noise (16)(17)(18)(19). As one of the most intuitive environmental factor, it is well-known that light may exert a signi cant impact on patients' physical and psychological well-being in various direct or indirect ways (20).…”
Section: Discussionmentioning
confidence: 99%
“…(1) The perceived IAQ assessment was based on the MM 040 questionnaire [25]. The questionnaire has been validated by school staff [13] and was also developed for office workers [26], hospital staff [27], and school pupils [28], all of them with a different combination of questions. In our study, we asked about complaints concerning stuffy "bad" air, dry air, insufficient ventilation, smell of mold or an earthen cellar, other unpleasant odors, dust or dirt in the work environment over the last three months.…”
Section: Assessments Of Iaqmentioning
confidence: 99%
“…A component of the indoor environment is indoor air. Poor indoor air quality (IAQ) refers objectively to contaminants in the air and inadequate ventilation [11,12] whereas subjectively it is often perceived as stuffy air, dry air, insufficient ventilation, and dust or dirt, as reported by the staff in Finnish schools [13]. As noted, interactions between the factors exist in addition to large individual differences, presenting challenges to an evaluation [8,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…19 Previous studies indicate a higher prevalence of self-reported health symptoms in hospitals than in offices. [20][21][22] Dry eyes and headaches are among the most reported building-related symptoms.…”
Section: Introductionmentioning
confidence: 99%